Methacrylic resin composition and resin molded body
By using light scattering agents of specific particle sizes and wavelength adjusters in the methacrylate resin composition, the problem that external components in the prior art are difficult to take into account between high brightness and transparent gloss, and a good balance between high brightness and transparent gloss is achieved.
Patent Information
- Application Number
- JP2023159196
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to ensure that external components such as automotive light covers maintain a transparent and glossy appearance when the light source is closed while maintaining high brightness.
A methacrylate resin composition containing a light scattering agent and a wavelength adjuster of a specific particle size is used, and the average particle size of the light scattering agent of the composition is between 200 nm and 700 nm, the mass ratio of the light scattering agent is between 4.0 ppm and 90 ppm, and the mass ratio of the wavelength adjuster is between 300% and 6000%.
The external components are achieved with high brightness when the light source is turned on, and a transparent and glossy appearance when the light source is turned off, ensuring external visibility and design aesthetics.
Smart Images

Figure 2025050413000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a methacrylic resin composition and a resin molded article. The above methacrylic resin composition can preferably provide a resin molded article having excellent external visibility, and the above resin molded article preferably has excellent external visibility due to excellent brightness when the light source is turned on, and excellent transparency and gloss when the light source is turned off. [Background technology]
[0002] Methacrylic resins are lighter than glass and have an excellent balance of transparency, weather resistance, mechanical properties, and processability among industrialized synthetic resins, and therefore are used in applications such as interior and exterior components for vehicles, lamp covers for illumination lamps, and light guides for surface light source devices (hereinafter simply referred to as "interior and exterior components for vehicles, etc."). In particular, methacrylic resin compositions have been adopted in recent applications for interior and exterior components for vehicles, such as vehicle lamp covers (hereinafter simply referred to as "lamp covers"), such as tail lamp covers, stop lamp covers, high-mount stop lamp covers, rear lamp covers, and rear combination lamp covers, as well as vehicle components such as visors, meter panels, display parts, and pillars. In applications such as vehicle interior and exterior components, particularly lamp covers, there is an increasing demand for resin compositions that emit high brightness when the light source is turned on from the viewpoint of external visibility, and as a technology for improving the brightness of light guides, Patent Document 1 discloses a methacrylic resin composition that contains a specific amount of titanium dioxide with a specific particle size as a light diffusing agent in a methacrylic resin, resulting in a well-balanced combination of transparency and brightness. Also, as in Patent Document 2, the use of a resin light guide plate containing a diffusing agent as a lamp cover has been considered. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 172243 [Patent Document 2] JP 2012-064533 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, Patent Document 1 considers the use of a methacrylic resin composition having an excellent balance between transparency, brightness, low colorability, and transparency and brightness, and a molded body suitable for a lamp cover for the outer cover of a lamp, and states that additives such as colorants may be contained within a range that does not impair the effect, and Patent Document 2 states that it is desirable to apply a color according to the light-emitting function. However, no specific method has been disclosed or considered for what type and how much of a light diffuser should be added when actually coloring a resin composition combined with a light diffuser, and what type and how much of an additive should be added, and how to combine them to create a resin composition that has high brightness and appears in the desired color when the light source is turned on, and that can be used to create a molded body that is transparent when the light source is turned off.
[0005] On the other hand, when a colored resin composition is arranged as an outer cover furthest from a light source, such as a brake light cover for a vehicle, the luminance tends to decrease due to light absorption by the colorant, reflection loss on the surface of the molded body, etc., and there is a strong demand for a resin composition that can be recognized from the outside while maintaining a higher luminance and that can fully function as a brake light. In addition, from the viewpoint of design, transparency and glossiness are required when the light source is turned off, and a resin composition that does not look cloudy and can be used to form a molded body with transparency and glossiness is required.
[0006] That is, an object of the present invention is to provide a methacrylic resin composition for producing a resin molded article having an excellent balance between luminance and transparency when the light source is turned on. [Means for solving the problem]
[0007] That is, the present invention is as follows. [1] A methacrylic resin, A light diffusing agent having an average particle size of 200 nm or more and 700 nm or less; At least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents, which have a maximum absorption wavelength at a wavelength of 440 to 600 nm in a wavelength range of 380 to 780 nm; Contains The mass ratio of the light diffusing agent is more than 4.0 ppm by mass and less than 90 ppm by mass with respect to 100% by mass of the methacrylic resin composition, The mass ratio of the wavelength adjusting agent is 300 ppm by mass or more and less than 6000 ppm by mass with respect to 100% by mass of the methacrylic resin composition. A methacrylic resin composition comprising: [2] The methacrylic resin composition according to [1], wherein the methacrylic resin contains 90% by mass or more and 99.9% by mass or less of methyl methacrylate monomer units and 0.1% by mass or more and 10% by mass or less of other vinyl monomer units copolymerizable with methyl methacrylate, relative to 100% by mass of the methacrylic resin, and has a weight average molecular weight of 90,000 or more and 200,000 or less. [3] The methacrylic resin composition according to [2], having a Vicat softening temperature of 102°C or higher and 130°C or lower. [4] A resin molded product obtained by molding a methacrylic resin composition containing a methacrylic resin, a light diffusing agent having an average particle size of 200 nm to 700 nm in an amount of 2 ppm by mass to 90 ppm by mass, and at least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents having a maximum absorption wavelength in the range of 440 to 600 nm in a wavelength range of 380 to 780 nm, Total light transmittance (Tt) in the thickness direction, measured in accordance with ISO13468, is 14% or more and less than 30%. The haze value (H) in the thickness direction measured in accordance with ISO14782 is 1.0% or more and 11% or less, and A resin molding, characterized in that the yellowness index (YI) in the thickness direction, the total light transmittance (Tt), and the haze value (H), measured in accordance with ISO17223, satisfy the following formulas (1) and (2): 0.11≦H / Tt≦0.8 (1) 25≦YI / H≦150 (2) [5] The resin molded article according to [4], which is used as a tail lamp cover, a stop lamp cover, a high mount stop lamp cover, a rear lamp cover, or a rear combination lamp cover. Effect of the Invention
[0008] According to the present invention, there can be provided a methacrylic resin composition for producing a resin molded article which has excellent external visibility due to excellent brightness when the light source is turned on, and excellent transparency and gloss when the light source is turned off. The resin molded article of the present invention has excellent designability with transparency and gloss when the light source is off, and emits high brightness when the light source is on, resulting in excellent external visibility, i.e., an excellent balance between transparency and brightness. In addition, it has excellent light resistance, and is therefore suitable as a vehicle exterior member, a lamp cover for an illumination lamp, and a light guide for a surface light source device, in particular a vehicle lamp cover for a vehicle exterior member. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, "(meth)acrylic acid" means at least one selected from "acrylic acid" and "methacrylic acid". In this specification, "monomer" means an unpolymerized compound, and "monomer unit" means a unit derived from the monomer formed by polymerization of the monomer. The monomer unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by treating the polymer. In this specification, "% by mass" indicates the mass percentage of a specific component contained in a total amount of 100% by mass. In this specification, the term "combination lamp cover" refers to a lamp cover that is provided on the front side of the light source of a combination lamp in a vehicle such as an automobile or motorcycle so as to cover the front of the light source, and means a lamp cover that is constructed by combining a lamp cover part that substantially does not contain a light diffusing agent with a lamp cover part that contains a light diffusing agent. As used herein, "vehicle" means a wheeled vehicle.
[0010] The present invention will be described in detail below, but the present invention is not limited to these embodiments.
[0011] The present invention includes a methacrylic resin composition according to a first embodiment, and a resin molded article according to a second embodiment, and may further be a vehicle lamp cover according to a third embodiment.
[0012] <Methacrylic resin composition> The methacrylic resin composition according to the first embodiment will now be described. The methacrylic resin composition of the present embodiment contains a methacrylic resin (preferably a transparent methacrylic resin), a light diffusing agent having an average particle size of 200 nm or more and 700 nm or less, as described below, and at least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents, which have a maximum absorption wavelength at a wavelength of 440 to 600 nm in a wavelength range of 380 to 780 nm, wherein the mass ratio of the light diffusing agent is more than 4.0 ppm by mass and less than 90 ppm by mass with respect to 100% by mass of the methacrylic resin composition, and the mass ratio of the wavelength adjusting agent is 300 ppm by mass or more and less than 6,000 ppm by mass with respect to 100% by mass of the methacrylic resin composition. The methacrylic resin composition of the present embodiment contains the methacrylic resin, and the obtained resin molded article has excellent transparency, light resistance, and heat deformation resistance. The methacrylic resin composition contains more than 4 ppm by mass and less than 90 ppm by mass of the light diffusing agent having an average particle size of 200 nm or more and 700 nm or less, and the obtained resin molded article has an excellent balance between transparency when the light source is turned off and brightness when the light source is turned on. The methacrylic resin composition of the present embodiment contains at least one of the wavelength regulators selected from the group consisting of azo, anthraquinone, perinone, methine, and quinophthalone, which have a maximum absorption wavelength of 440 to 600 nm at a wavelength of 380 to 780 nm, at a wavelength of 300 ppm by mass or more and less than 6000 ppm by mass, so that the resin molded article can be a coloring material having a brightness that is easily visible even from a distance when the light source is turned on, and can be a resin molded article having gloss and transparency when the light source is turned off. The methacrylic resin composition of this embodiment is preferably red. Here, red refers to the color of 1:pR to 3:yR in the PCCS24 color wheel. When the methacrylic resin composition is fed to an injection molding machine using a mold with a polished number of 8000, the molding temperature is set to 250°C, the mold temperature is set to 70°C, and a molded body having a thickness of 3.18 mm is obtained, and it is more preferable that the chromaticity range of the color name red described in JIS D5500 is satisfied as a result of measurement in a 2° field transmission mode using an A light source. The color of the methacrylic resin composition can be adjusted by the composition of the methacrylic resin, the type, average particle size and mass ratio of the light diffusing agent contained in the methacrylic resin composition, the type and mass ratio of the wavelength adjusting agent, and the combination method of the light diffusing agent and the wavelength adjusting agent.
[0013] In the methacrylic resin composition of the present embodiment, the lower limit of the mass ratio of the light diffusing agent is preferably more than 4.5 mass ppm, more preferably 6.5 mass ppm or more, and even more preferably 7.2 mass ppm or more, relative to 100 mass% of the methacrylic resin composition, when a light diffusing agent that is an inorganic compound with an average particle size of 200 nm to 300 nm is used, from the viewpoint of excellent brightness and balance between transparency and brightness of the obtained resin molded product. Also, when a light diffusing agent that is an inorganic compound with an average particle size of more than 300 nm to 700 nm is used, the lower limit is preferably 8 mass ppm or more, more preferably 10 mass ppm or more, and even more preferably 15 mass ppm or more. From the viewpoint of the transparency of the resin molded product obtained and the balance between transparency and brightness, when a light diffusing agent that is an inorganic compound having an average particle size of 200 nm to 300 nm is used, the upper limit of the mass proportion of the light diffusing agent is preferably less than 20 ppm by mass, more preferably 18 ppm by mass or less, and even more preferably 16 ppm by mass or less, relative to 100 mass% of the methacrylic resin composition. When a light diffusing agent that is an inorganic compound having an average particle size of more than 300 nm to 700 nm is used, the upper limit of the mass proportion of the light diffusing agent is preferably less than 90 ppm by mass, more preferably 80 ppm by mass or less, and even more preferably 70 ppm by mass or less. It is also preferable that the light diffusing agent having an average particle size of 350 to 700 nm is contained in an amount of 10 ppm by mass to 90 ppm by mass. In a further preferred embodiment of the methacrylic resin composition of the present embodiment, from the viewpoint of obtaining a resin molded product having a curved shape with excellent transparency, brightness, low colorability, and a balance between transparency and brightness, the methacrylic resin composition contains a light diffusing agent having an average particle size of 200 to 300 nm in an amount of 6.5 to 18 ppm by mass, more preferably 7.2 to 16 ppm by mass, based on 100% by mass of the methacrylic resin composition. Also, the methacrylic resin composition contains a light diffusing agent having an average particle size of 350 to 600 nm in an amount of 12 to 90 ppm by mass, more preferably 15 to 80 ppm by mass. The above upper and lower limits can be combined in any manner.
[0014] In the methacrylic resin composition of the present embodiment, the lower limit of the refractive index difference between the methacrylic resin (preferably a methacrylic transparent resin) and the light diffusing agent is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and particularly preferably 0.8 or more, from the viewpoint of maintaining the brightness of the obtained resin molded body (for example, a lamp cover) well. The upper limit of the refractive index difference is preferably 3.0 or less, more preferably 2.0 or less, from the viewpoint of maintaining the transparency of the obtained resin molded body (for example, a lamp cover) well. The upper and lower limits can be arbitrarily combined. Specifically, the refractive index difference between the methacrylic resin (preferably a methacrylic transparent resin) and the light diffusing agent is preferably 0.1 to 3.0, more preferably 0.3 to 2.0, and even more preferably 0.8 to 2.0. The method for measuring the refractive index of the light diffusing agent can be selected arbitrarily depending on the composition and form of the light diffusing agent, but when the light diffusing agent is an inorganic solid, it is measured using the minimum deviation method with an Abbe refractometer, precision spectrometer, or precision refractometer. When the light diffusing agent is an organic solid that dissolves or disperses in a solvent, it can be dissolved or dispersed in a solvent with any refractive index, and the refractive index of the solvent that shows the maximum value of the spectral transmittance can be taken as the refractive index of the light diffusing agent. When the light diffusing agent is an organic solid that is insoluble or not dispersed in a solvent, the refractive index of the light diffusing agent is calculated from the refractive index of the raw material depending on the raw material composition of the light diffusing agent. In this specification, the "refractive index" may be a value measured in accordance with JIS K0062 using sodium d line (589 nm).
[0015] (Methacrylic resin) The methacrylic resin is one of the components of the methacrylic resin composition of the present embodiment. In order to improve the flowability, transparency, yellowness, and heat deformation resistance, the above-mentioned methacrylic resin is preferably a homopolymer of a methacrylic acid ester (preferably methyl methacrylate) or a copolymer containing a monomer unit derived from a methacrylic acid ester (preferably methyl methacrylate). Among them, from the viewpoint of ensuring excellent light resistance, a copolymer containing a monomer unit derived from a methacrylic acid ester (e.g., methyl methacrylate) and a monomer unit derived from a monomer not containing an aromatic ring that can be copolymerized with a methacrylic acid ester (e.g., methyl methacrylate) (e.g., a monomer not containing an aromatic ring among other monomers described below) is preferred, and a copolymer consisting only of a monomer unit derived from a methacrylic acid ester (e.g., methyl methacrylate) and a monomer unit derived from a monomer not containing an aromatic ring that can be copolymerized with a methacrylic acid ester (e.g., methyl methacrylate) (e.g., a monomer not containing an aromatic ring among other monomers described below) is more preferred.
[0016] The copolymer is preferably a copolymer in which the mass ratio of monomer units derived from methacrylic acid esters (preferably methyl methacrylate) is 75% by mass or more relative to 100% by mass of the methacrylic resin. The copolymer is more preferably a copolymer containing 85% by mass or more and less than 100% by mass of monomer units derived from methacrylic acid esters (preferably methyl methacrylate) and more than 0% by mass and 15% by mass or less of monomer units derived from other monomers (preferably monomers not containing aromatic rings among the other monomers described below) relative to 100% by mass of the methacrylic resin, and even more preferably a copolymer containing 90% by mass or more and 99.9% by mass or less of monomer units derived from methacrylic acid esters (preferably methyl methacrylate) and 0.1% by mass or more and 10% by mass or less of monomer units derived from other monomers (preferably monomers not containing aromatic rings among the other monomers described below). the copolymer containing 93% by mass or more and 99.7% by mass or less of monomer units derived from a methacrylic acid ester (preferably methyl methacrylate) and 0.3% by mass or more and 7% by mass or less of monomer units derived from another monomer (preferably a monomer not containing an aromatic ring among the other monomers described below); and the copolymer containing 96% by mass or more and 99.5% by mass or less of monomer units derived from a methacrylic acid ester (preferably methyl methacrylate) and 0.5% by mass or more and 4% by mass or less of monomer units derived from another monomer (preferably a monomer not containing an aromatic ring among the other monomers described below).
[0017] The other monomer is preferably a monomer copolymerizable with a methacrylic acid ester (preferably methyl methacrylate). The other monomers constituting the monomer units derived from the other monomers contained in the methacrylic resin include, but are not limited to, acrylic acid esters (preferably acrylic acid esters not containing aromatic rings), such as acrylic acid ester monomers having one acrylate group (preferably acrylic acid ester monomers not containing aromatic rings) such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, and lauryl acrylate. Methyl acrylate, ethyl acrylate, and butyl acrylate are preferred because they are easily available. In addition, it is preferred to use a monomer not containing an aromatic ring from the viewpoint of long-term use properties.
[0018] When using an acrylic acid ester monomer having one acrylate group (for example, an acrylic acid ester monomer having one acrylate group that does not contain an aromatic ring), from the viewpoint of good fluidity, the mass ratio of the monomer unit derived from the acrylic acid ester monomer having one acrylate group is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably 1 mass% or more, relative to 100 mass% of the methacrylic resin. From the viewpoint of good heat deformation resistance, the mass ratio of the monomer unit derived from the acrylic acid ester monomer having one acrylate group is preferably 8 mass% or less, more preferably 5 mass% or less, and even more preferably 4 mass% or less, relative to 100 mass% of the methacrylic resin. In particular, when methyl acrylate is used as the other monomer, it is preferable that the monomer unit derived from methyl acrylate is contained in an amount of 0.5 to 6 mass% relative to 100 mass% of the methacrylic resin, and when ethyl acrylate is used, it is preferable that the monomer unit derived from ethyl acrylate is contained in an amount of 0.5 to 5 mass% relative to 100 mass% of the methacrylic resin.
[0019] Other examples of the other monomers include acrylic acid ester monomers such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and other ethylene glycol or oligomers thereof having two or more (meth)acrylate groups, esterified with acrylic acid or methacrylic acid at both terminal hydroxyl groups; neopentyl glycol di(meth)acrylate, di(meth)acrylate, and other two alcohol hydroxyl groups esterified with acrylic acid or methacrylic acid; and trimethylolpropane, pentaerythritol, and other polyhydric alcohol derivatives esterified with acrylic acid or methacrylic acid. Among these, from the viewpoint of long-term use properties, acrylic acid ester monomers not containing aromatic rings are preferred. In this specification, a methacrylic acid ester refers to a compound having only one methacrylate group, and a methacrylic acid ester having a plurality of methacrylate groups is regarded as another monomer copolymerizable with the methacrylic acid ester.
[0020] From the viewpoints of ensuring fluidity during injection molding and maintaining transparency, it is preferable that when a monomer having two (meth)acrylate groups is used, the monomer unit derived from the monomer having two (meth)acrylate groups is 0.4 mass% or less relative to 100 mass% of the above-mentioned methacrylic resin. When a monomer having three (meth)acrylate groups is used, it is 0.2 mass% or less. When a monomer having four or more (meth)acrylate groups is used, it is 0.1 mass% or less.
[0021] Furthermore, examples of the other monomers other than the acrylic acid ester monomer include, but are not limited to, α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and their alkyl esters such as maleic acid, fumaric acid, itaconic acid, and cinnamic acid; styrene-based monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, and isopropenylbenzene (α-methylstyrene); 1-vinylnaphthalene, 2-vinylnaphthalene Examples of the monomers include aromatic vinyl compounds such as 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic anhydrides such as maleic anhydride and itaconic anhydride; maleimide, N-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; amides such as acrylamide and methacrylamide; and polyfunctional monomers such as divinylbenzene. Among these, from the viewpoint of heat deformation resistance, N-substituted maleimide and methacrylic acid are preferred, and from the viewpoint of suppressing yellowness, it is preferred to use a monomer that does not contain an aromatic ring, specifically N-cyclohexylmaleimide and methacrylic acid.
[0022] The mass ratio of other monomer units (preferably monomer units having a vinyl group) copolymerizable with the above-mentioned methacrylic acid ester constituting the methacrylic resin is preferably 0.1 mass% or more and 20 mass% based on 100 mass% of the methacrylic resin. By setting the mass ratio of the monomer unit derived from another monomer (preferably a monomer having a vinyl group) copolymerizable with the methacrylic acid ester to 0.1 mass% or more relative to 100 mass% of the above methacrylic resin, the flowability and heat resistance can be improved, and by setting it to 20 mass% or less, good flowability and toughness can be ensured. The mass ratio is preferably 0.5 to 17 mass%, more preferably 1 to 10 mass%, and further preferably 3 to 8 mass%. The above other monomers may be used alone or in combination of two or more.
[0023] Among the above other monomers, from the viewpoint of not impairing the inherent performance of the methacrylic resin and of providing excellent thermal decomposition resistance of the obtained resin molded article, alkyl acrylates having 1 to 8 carbon atoms in the alkyl group are preferred, and methyl acrylate, ethyl acrylate, and n-butyl acrylate are more preferred, and from the viewpoint of ensuring the heat distortion temperature resistance of the molded article, methyl acrylate and ethyl acrylate are even more preferred.
[0024] The polymerization method for polymerizing the monomer components is not particularly limited, and any known polymerization method such as suspension polymerization, solution polymerization, or bulk polymerization can be used. Among these, suspension polymerization is preferred because it can be carried out at a relatively low temperature, can reduce the amount of energy, and can be easily post-processed to prepare pellets for molding.
[0025] The polymerization initiator used when polymerizing the monomer components is not particularly limited, and for example, known radical polymerization initiators such as known azo compounds such as azobisisobutyronitrile, 1,1-di(t-butylperoxy)cyclohexane, and known peroxides such as lauroyl peroxide can be used. The polymerization initiator may be used alone or in combination of two or more kinds.
[0026] When polymerizing the monomer components, a chain transfer agent can be used to adjust the molecular weight of the methacrylic resin. The type of the chain transfer agent is not particularly limited, and preferred examples include mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, and 2-ethylhexyl thioglycolate. The chain transfer agent may be used alone or in combination of two or more kinds.
[0027] The polymerization initiator and the chain transfer agent can be added appropriately depending on the molecular weight of the target methacrylic resin, but are generally used in an amount of 0.001 to 5 parts by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin.
[0028] Other methods for controlling the molecular weight include a method of changing the polymerization method, a method of adjusting the amounts of the polymerization initiator, the above-mentioned chain transfer agent, the polymerization initiator, etc., and a method of changing various polymerization conditions such as the polymerization temperature. These molecular weight control methods may be used alone or in combination of two or more.
[0029] The weight average molecular weight (Mw) of the methacrylic resin is not particularly limited, and can be appropriately set according to the shape and size of the resin molded body to be obtained, or the processing method of the resin molded body. The weight average molecular weight (Mw) is generally set in the range of 20,000 to 1,000,000, and in the application of injection molding, it is set in the range of 50,000 to 200,000. From the viewpoint of required strength and solvent resistance, the weight average molecular weight (Mw) of the methacrylic resin is preferably 90,000 or more, more preferably 92,000 or more, and even more preferably 95,000 or more, and from the viewpoint of ensuring good molding flowability, it is preferably 190,000 or less, more preferably 180,000 or less, and even more preferably 150,000 or less. In this specification, the weight average molecular weight is a value measured by gel permeation chromatography using standard polymethyl methacrylate as a standard sample.
[0030] The mass ratio of the methacrylic resin to 100% by mass of the methacrylic resin composition of the present embodiment is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, from the viewpoints of excellent transparency, weather resistance, and heat deformation resistance. Also, from the viewpoints of exhibiting good moldability as a color-developing body and external visibility when lit, it is preferably 99.98% by mass or less, more preferably 99.95% by mass or less, and particularly preferably 99.9% by mass or less.
[0031] (Light diffusing agent) The light diffusing agent is one of the components of the methacrylic resin composition of the present embodiment. When the methacrylic resin composition of the present embodiment contains the light diffusing agent, the obtained resin molded article and lamp cover have an excellent balance between the gloss and transparency when the light source is turned off, and the luminance when the light source is turned on.
[0032] When the resin molded body containing the methacrylic resin composition of the present embodiment is used for edge-light type vehicle interior / exterior members, surface light source device light guides, etc., in the above resin molded body, when the incident light from the light source hits the light diffusing agent and scatters, if the particle diameter of the light diffusing agent is too small, the proportion of forward scattering increases and the proportions of orthogonal scattering and backward scattering tend to decrease, and conversely, if the particle diameter of the light diffusing agent is too large, the proportion of backward scattering increases and the proportions of forward scattering and orthogonal scattering decrease. That is, if the particle diameter of the light diffusing agent is too small or too large, the brightness of orthogonal scattering required for edge-light type vehicle interior / exterior members and surface light source device light guides tends to be insufficient. In particular, the influence is remarkable in lamp covers having curved shapes. In addition, the smaller the particle size of the light diffusing agent, the more the relatively short-wavelength blue light in the wavelength range of the incident visible light is scattered by the fine particles, and the more likely it is to become yellowish. Therefore, if the particle size of the light diffusing agent is increased, the light diffusibility may decrease, and it is necessary to increase the amount of the light diffusing agent to obtain sufficient brightness. If the amount of the light diffusing agent is increased, the brightness increases, but the transparency decreases, and the balance between transparency and brightness tends to be impaired. Furthermore, the smaller the difference in refractive index between the light diffusing agent and the methacrylic resin (preferably a methacrylic transparent resin), the more the hue of the light observed near the light source incident end face of the light guide and the light observed at a position away from the incident end face changes. However, in the methacrylic resin composition of the present embodiment, by optimizing the combination of the average particle size of the light diffuser and the content ratio of the light diffuser, it is possible to achieve excellent luminance not only in terms of orthogonal scattering but also over all angles measured relative to the surface normal of the obtained resin molded article. In particular, the above effects are prominent in lamp covers having curved shapes; therefore, by optimizing the combination of the particle size of the light diffuser, the refractive index difference between the light diffuser and the transparent resin, and the content of the light diffuser, it is possible to achieve excellent brightness not only in terms of rectangular scattering, but also in terms of brightness over all angles measured relative to the surface normal of the lamp cover.
[0033] The lower limit of the average particle size of the light diffusing agent is 200 nm or more from the viewpoint of excellent brightness and low coloring of the resulting resin molded article, and the upper limit of the average particle size is 700 nm or less, preferably 600 nm or less, more preferably 500 nm or less, and even more preferably 280 nm or less, from the viewpoint of excellent transparency of the resulting resin molded article. The average particle size of the light diffusing agent can be measured in accordance with JIS Z8825.
[0034] The light diffusing agent may be any known fine particle such as titanium dioxide, aluminum oxide, zinc oxide, zinc sulfide, barium sulfate, etc. Among these, from the viewpoint of achieving even better transparency and brightness, titanium dioxide, aluminum oxide, zinc oxide, and barium sulfate are preferred, aluminum oxide and titanium dioxide are more preferred, and titanium dioxide is even more preferred. In particular, for applications of lamp covers having curved surfaces, aluminum oxide and titanium dioxide particles having an average particle size of 200 to 500 nm are preferred, and titanium dioxide particles having an average particle size of 220 to 300 nm are more preferred. Even in lamp covers having curved surfaces, the incident light is not significantly emitted from the curved surface, so that transparency, brightness, and a balance between transparency and brightness can be achieved.
[0035] From the viewpoint of achieving a better balance between the transparency and brightness of the resin molding, the particle size distribution of the light diffusing agent is preferably such that the ratio (D90 / D10) of the particle size at which the cumulative frequency is 90% (D90) to the particle size at which the cumulative frequency is 10% (D10) in a cumulative frequency distribution curve of the particle sizes of the light diffusing agent is 1.2 or more and 2.5 or less, more preferably 1.5 or more and 2.3 or less, and even more preferably 1.7 or more and 2.1 or less. The cumulative frequency distribution curve of the particle size of the light diffusing agent can be measured in accordance with JIS Z8825.
[0036] As D90 / D10 approaches 1, the particle size distribution of the light diffuser becomes sharper, and the light diffusion efficiency of the resin molded body tends to increase. Conversely, the balance between the transparency and brightness of the resin molded body tends to decrease. From this viewpoint, the lower limit of D90 / D10 is preferably 1.2 or more, more preferably 1.5 or more, and even more preferably 1.7 or more. The upper limit of D90 / D10 is preferably 2.5 or less, more preferably 2.3 or less, and even more preferably 2.1 or less, from the viewpoint that as D10 decreases and D90 / D10 increases, the balance between transparency and brightness of the obtained resin molded article tends to decrease, and conversely, as D90 increases and D90 / D10 increases, the light diffusion efficiency tends to decrease and the brightness of the obtained resin molded article tends to decrease.
[0037] A resin molded product containing a methacrylic resin composition having a D90 / D10 of 2.5 or less (more preferably 2.3 or less) and containing a light diffusing agent having an average particle size of 200 nm or more and 300 nm or less in an amount of more than 4.0 ppm by mass and less than 90 ppm by mass (more preferably 5 ppm by mass or more and 60 ppm by mass or less, and even more preferably 6.0 ppm by mass or more and 20 ppm by mass or less) relative to 100 mass% of the methacrylic resin composition has particularly excellent transparency, brightness, and a balance between transparency and brightness.
[0038] (Wavelength Adjustment Agent) The wavelength adjusting agent is one of the components of the methacrylic resin composition of the present embodiment. The wavelength adjusting agent is at least one selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based and quinophthalone-based agents, which have a maximum absorption wavelength at 440 to 600 nm in a wavelength range of 380 to 780 nm. The wavelength of maximum absorption can be measured by a spectrophotometer.
[0039] From the viewpoint of stability during thermal processing, the wavelength adjusting agent is preferably anthraquinone-based or perinone-based. When an inorganic compound, particularly titanium dioxide, is used as a light diffusing agent, depending on the wavelength regulator, the wavelength regulator may not be able to exhibit the good weather resistance that it originally has. Even when an inorganic light diffusing agent and a wavelength regulator are combined, excellent weather resistance can be exhibited, so it is more preferable to use a perinone-based wavelength regulator. Even when an inorganic light diffusing agent and a wavelength regulator are combined, excellent weather resistance can be exhibited, so it is more preferable that at least one wavelength regulator selected from the group consisting of azo-based, anthraquinone-based, perinone-based, and methine-based wavelength regulators has a part of hydrogen atoms in the chemical structure replaced by halogen atoms, and it is particularly preferable to use a perinone-based wavelength regulator in which a part of hydrogen atoms in the chemical structure of the wavelength regulator is replaced by halogen atoms.
[0040] As long as the wavelength regulator contains at least one wavelength regulator selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based compounds having a maximum absorption wavelength in the wavelength range of 440 to 600 nm in the wavelength range of 380 to 780 nm, it may be used in combination with other wavelength regulators in a form of two or more types, or may be used solely with at least one wavelength regulator selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based compounds having a maximum absorption wavelength in the wavelength range of 440 to 600 nm in the wavelength range of 380 to 780 nm. In addition, at least one of the wavelength adjusting agents selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents having a maximum absorption wavelength in the wavelength range of 440 to 600 nm in a wavelength range of 380 to 780 nm may be used alone or in combination of two or more types.
[0041] The mass ratio of the wavelength regulator is 300 mass ppm or more and less than 6000 mass ppm, preferably 300 mass ppm or more and 5000 mass ppm or less, more preferably 1000 mass ppm or more and 4000 mass ppm or less, based on 100 mass% of the methacrylic resin composition in order to balance the transparency and the color development of red, or to obtain a red color with good light resistance. In order to obtain a red color suitable for automobiles as defined in JIS D5500, more preferably 0.12 mass% or more and even more preferably 0.15 mass% or more. In order to obtain good transparency and to obtain good luminance at the time of light entry even if light is absorbed by the wavelength regulator, the mass ratio is preferably 4000 mass ppm or less, more preferably 3000 mass ppm or less, and even more preferably 2000 mass ppm or less.
[0042] (Methacrylic resin composition manufacturing method) The methacrylic resin composition of the present embodiment can be prepared by mixing the mixture containing the methacrylic resin, the light diffusing agent, and the wavelength adjusting agent. The mixing method is not particularly limited, and melt kneading method, solvent kneading method, dry blending method, etc. are used, and from the viewpoint of productivity, melt kneading method and dry blending method are preferably used. As the equipment used for mixing, a normal mixer, kneader, etc. can be used, and specifically, a single-screw kneading extruder, a twin-screw kneading extruder, a ribbon blender, a Henschel mixer, a Banbury mixer, a drum tumbler, etc. can be mentioned. In the methacrylic resin composition of the present embodiment, when a twin-screw kneading extruder is used, the light diffusing agent and the wavelength adjusting agent can be dispersed more uniformly in the resin composition without aggregation, and the obtained resin molded product has an excellent balance of transparency and brightness and excellent uniformity of properties. Specifically, a mixture containing the above-mentioned methacrylic resin, the above-mentioned light diffusing agent, and the above-mentioned wavelength adjusting agent is melted and mixed using a twin-screw kneading extruder in a temperature range of not less than the glass transition point of the above-mentioned methacrylic resin + 50°C and not more than the glass transition point + 190°C, thereby obtaining a pellet-shaped methacrylic resin composition. By using a twin-screw kneading extruder to melt and mix the mixture containing the methacrylic resin, the light diffusing agent, and the wavelength adjusting agent at a temperature in the range of the glass transition point of the methacrylic resin + 50°C or more and the glass transition point + 190°C or less, it is possible to suppress deterioration and coloration of the mixture due to heating and deterioration of the wavelength adjusting agent, resulting in a resin molded product with excellent hue stability.
[0043] The methacrylic resin composition of the present embodiment may contain, as necessary, various additives other than the methacrylic resin, the light diffusing agent, and the wavelength adjusting agent, such as known additives such as antioxidants, stabilizers, UV absorbers, lubricants, processing aids, antistatic agents, dyes that exhibit a maximum absorption wavelength in a wavelength range other than 450 to 600 nm in a wavelength range of 380 to 780 nm, impact resistance aids, foaming agents, fillers, and matting agents, within a range that does not impair the effects of the present invention. The methacrylic resin composition of the present embodiment may be a mixture consisting of only the methacrylic resin, the light diffusing agent, and the wavelength adjusting agent.
[0044] <Resin molded body> The resin molded article according to the second embodiment will now be described. The resin composition form may be a resin molding obtained by molding a methacrylic resin composition containing a methacrylic resin, a light diffusing agent having an average particle size of 200 nm or more and 700 nm or less at 2 ppm by mass or more and 90 ppm by mass or less (i.e., a light diffusing agent having an average particle size of 200 nm or more and 700 nm or less at 2 ppm by mass or more and 90 ppm by mass or less relative to 100 mass% of the methacrylic resin composition), and at least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents having a maximum absorption wavelength at 440 to 600 nm in a wavelength range of 380 to 780 nm. The resin molded product is preferably a resin molded product obtained by molding the methacrylic resin composition of the present embodiment described above. That is, the resin molded product of the present embodiment is preferably a resin molded product containing the methacrylic resin composition of the present embodiment described above. The shape of the resin molded body may be a flat plate or a plate having a concavely curved surface or a convexly curved surface.
[0045] The resin molded product is a resin molded product obtained by molding a methacrylic resin composition containing a methacrylic resin (preferably a transparent methacrylic resin), a light diffusing agent having an average particle size of 200 nm to 700 nm in an amount of 2 ppm by mass to 90 ppm by mass, and at least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents, the wavelengths of which have a maximum absorption wavelength at 440 to 600 nm in a wavelength range of 380 to 780 nm; Total light transmittance (Tt) in the thickness direction, measured in accordance with ISO13468, is 14% or more and less than 30%. The haze value (H) in the thickness direction measured in accordance with ISO14782 is 1.0% or more and 11% or less, and The resin molded article may have a yellowness index (YI), total light transmittance (Tt) and haze value (H) in the thickness direction measured in accordance with ISO17223 that satisfy the following formulas (1) and (2). 0.11≦H / Tt≦0.8 (1) 25≦YI / H≦150 (2)
[0046] The lower limit of the yellowness index (YI) is preferably 15 or more, more preferably 25 or more, even more preferably 50 or more, even more preferably 200 or more, and particularly preferably 250 or more, from the viewpoint of preventing the lamp cover from taking on a bluish tint when the light source is turned on and achieving good low coloration, and from the viewpoint of the lamp cover being transparent when the light source is turned off and therefore less noticeable, and of exhibiting good red color even when light is guided. On the other hand, from the viewpoint of suppressing light absorption by the wavelength adjusting agent while producing a good red color, the upper limit is preferably 370 or less, more preferably 330 or less, even more preferably 300 or less, and particularly preferably 270 or less. The above yellowness can be achieved by optimizing the type of the methacrylic resin, the type, shape and content of the light diffusing agent, and the conditions of the production method of the methacrylic resin composition.
[0047] The resin molding is preferably a resin molding having a total light transmittance (Tt) in the thickness direction when the optical path length of transmitted light is 3 mm (hereinafter abbreviated as "total light transmittance") of 14% or more and less than 30% when measured in accordance with ISO 13468, a haze value (H) in the thickness direction when the optical path length of transmitted light is 3 mm (hereinafter abbreviated as "haze value") of 1.0% or more and 11% or less when measured in accordance with ISO 14782, and a yellowness index (YI) in the thickness direction when the optical path length of transmitted light is 3 mm (hereinafter abbreviated as "yellowness"), the total light transmittance (Tt) and the haze value (H) when measured in accordance with ISO 17223 satisfy the following formulas (1) and (2). 0.11≦H / Tt≦0.8 (1) 25≦YI / H≦150 (2) The total light transmittance, the haze value, and the yellowness index can be measured by the methods described in the Examples below. For example, the measurement sample may be a plate-shaped molded product of the methacrylic resin composition having a flat plate shape or a plate shape having a concave curved surface or a convex curved surface.
[0048] The lower limit of the H / Tt value is 0.11 or more, more preferably 0.15 or more, and even more preferably 0.20 or more, from the viewpoint of increasing light diffusion and improving the brightness and external visibility of the resin molded body when the light source is turned on. On the other hand, the upper limit of the H / Tt value is 0.8 or less, more preferably 0.7 or less, and even more preferably 0.6 or less, from the viewpoint of improving the transparency of the resin molded body when the light source is turned off. The above upper and lower limits can be arbitrarily combined. Specifically, the H / Tt value is preferably 0.11 to 0.8, more preferably 0.15 to 0.7, and even more preferably 0.20 to 0.6. The H / Tt value can be controlled by adjusting the type of the transparent resin, the type, shape and content of the light diffusing agent, and the conditions of the production method of the methacrylic resin composition.
[0049] The lower limit of the YI / H value is 25 or more, more preferably 35 or more, and even more preferably 40 or more, so that the resin molded body maintains good transparency when the light source is turned off and exhibits good color tone. On the other hand, the upper limit of the YI / H value is preferably 150 or less, more preferably 100 or less, and even more preferably 70 or less, so that good light diffusibility and good brightness are obtained. The above upper and lower limits can be arbitrarily combined, and for example, the YI / H value is preferably 25 to 150, more preferably 35 to 100, and even more preferably 40 to 70.
[0050] In this specification, the thickness direction of the resin molding refers to a direction approximately perpendicular to the surface of the resin molding. The total light transmittance (Tt) in the thickness direction when the optical path length of the transmitted light is 3 mm does not limit the thickness of the resin molding to 3 mm. The haze value (H) in the thickness direction when the optical path length of the transmitted light is 3 mm does not limit the thickness of the resin molding to 3 mm.
[0051] The lower limit of the total light transmittance of the resin molded body of this embodiment is preferably 11% or more, more preferably 14%, even more preferably 15% or more, and even more preferably 17% or more, from the viewpoint that the resin molded body has high transparency when the light source is turned off, and the design of lamps, vehicles, etc. is excellent. The upper limit of the total light transmittance of the resin molded body is not particularly limited, and is less than 30%, more preferably 27% or less, and even more preferably 25% or less, from the viewpoint that the resin molded body has excellent light diffusion properties and high brightness. The above upper and lower limits can be arbitrarily combined. The total light transmittance can be controlled by adjusting the type of the methacrylic resin, the type, shape and content of the light diffusing agent, and the type and amount of the wavelength adjusting agent.
[0052] The lower limit of the haze value of the resin molded body of this embodiment is preferably 1.0% or more, more preferably 2.0% or more, and even more preferably 3.0% or more, from the viewpoint that the resin molded body has excellent light diffusion properties and high brightness. The upper limit of the haze value of the resin molded body is preferably 11.0% or less, more preferably 9.0% or less, and even more preferably 8.0% or less, from the viewpoint that the brightness when the light source is turned on is good, and the resin molded body has a transparent feeling and can reduce the presence of the resin molded body when the light source is turned off, and therefore the design is excellent. The above upper and lower limits can be arbitrarily combined. Specifically, the haze value of the resin molded body is preferably 1.0 to 11.0%, more preferably 2.0 to 9.0%, and even more preferably 3.0 to 8.0%. The haze value can be controlled by adjusting the type of the methacrylic resin, the type, shape and content of the light diffusing agent, the type and content of the wavelength adjusting agent, and the thickness of the molded article.
[0053] In the resin molded product of this embodiment, the value (H / Tt value) obtained by dividing the haze value (H) by the total light transmittance (Tt) is an index of the transparency and brightness of the resin molded product, and preferably satisfies the following formula (1). Also, the value (YI / H value) obtained by dividing the yellowness index (YI) by the haze value (H) is an index of the uniformity of brightness and uniformity of hue of the resin molded product, and preferably satisfies the following formula (2). 0.11≦H / Tt≦0.8 (1) 25≦YI / H≦150 (2)
[0054] The lower limit of the H / Tt value is preferably 0.11 or more, more preferably 0.15 or more, and even more preferably 0.20 or more, from the viewpoint of improving the light diffusion property and the brightness and external visibility of the resin molded body when the light source is turned on. The upper limit of the H / Tt value is preferably 0.8 or less, more preferably 0.7 or less, and even more preferably 0.6 or less, from the viewpoint of improving the transparency of the resin molded body when the light source is turned off. The above upper and lower limits can be arbitrarily combined. Specifically, the H / Tt value is preferably 0.11 to 0.8, more preferably 0.15 to 0.7, and even more preferably 0.20 to 0.6. The H / Tt value can be controlled by adjusting the type of the methacrylic resin, the thickness of the molded article, the type, shape and content of the light diffusing agent, and the conditions of the production method of the methacrylic resin composition.
[0055] The lower limit of the YI / H value is preferably 25 or more, more preferably 35 or more, and even more preferably 40 or more, so that the resin molded body maintains good transparency while expressing good color tone when the light source is turned off. The upper limit of the YI / H value is preferably 150 or less, more preferably 120 or less, even more preferably 100 or less, and particularly preferably 70 or less, so that good light diffusibility and good brightness are obtained. The above upper and lower limits can be arbitrarily combined, but the YI / H value is preferably 25 to 150, more preferably 35 to 100, and even more preferably 40 to 70. The YI / H value can be controlled by adjusting the type of the methacrylic resin, the type, shape and content of the light diffusing agent, the thickness of the molded article, and the conditions of the production method of the methacrylic resin composition.
[0056] In the resin molded product of this embodiment, the lower limit of the content of the light diffusing agent contained in the methacrylic resin composition is preferably more than 4.5 mass ppm, more preferably 6.5 mass ppm or more, and even more preferably 7.2 mass ppm or more, relative to the total mass of the methacrylic resin composition, when a light diffusing agent having an average particle diameter of 200 nm or more and 300 nm or less is used, from the viewpoint of excellent transparency, brightness, and balance between transparency and brightness of the resin molded product. When a light diffusing agent having an average particle diameter of more than 300 nm is used, the lower limit is preferably 8 mass ppm or more, more preferably 10 mass ppm or more, and even more preferably 15 mass ppm or more. On the other hand, the upper limit of the content of the light diffusing agent is preferably less than 20 mass ppm, relative to the total mass of the methacrylic resin composition, from the viewpoint of excellent transparency, brightness, and balance between transparency and brightness of the resin molded product obtained, when a light diffusing agent having an average particle diameter of 200 nm or more and 300 nm or less is used, the upper limit is preferably less than 20 mass ppm, relative to the total mass of the methacrylic resin composition. More preferably, it is 18 mass ppm or less, and even more preferably, it is 16 mass ppm or less. When a light diffusing agent having an average particle size of more than 300 nm and not more than 900 nm is used, the content is preferably less than 90 ppm by mass, more preferably not more than 80 ppm by mass, and even more preferably not more than 70 ppm by mass. The above upper and lower limits can be combined in any combination.
[0057] In a more preferred embodiment of the resin molded article of this embodiment, from the viewpoint of excellent transparency, brightness, low colorability, and balance between transparency and brightness of the resin molded article, the mass ratio of the light diffusing agent having an average particle size of 200 to 300 nm is preferably more than 4 mass ppm and less than 20 mass ppm relative to 100 mass% of the methacrylic resin composition, and the mass ratio of the light diffusing agent having an average particle size of 350 to 700 nm is preferably 10 mass ppm or more and 90 mass ppm or less. The mass ratio of the light diffusing agent having an average particle size of 350 to 600 nm is preferably 12 mass ppm or more and 90 mass ppm or less, more preferably 15 mass ppm or more and 80 mass ppm or less. In a further preferred embodiment of the resin molded product of this embodiment, from the viewpoint of the brightness, low coloring property, and balance between transparency and brightness of the resin molded product having a curved shape, it is more preferable that the light diffusing agent having an average particle size of 200 to 300 nm is contained at a content ratio of more than 4.5 mass ppm and less than 18 mass ppm relative to the total mass of the methacrylic resin composition. In the resin molded product of this embodiment, from the viewpoint of the transparency, brightness, and balance between transparency and brightness of the resin molded product having a curved shape, it is more preferable that the light diffusing agent having an average particle size of 200 to 300 nm is contained at a content ratio of 6.5 mass ppm or more and 18 mass ppm or less, and more preferably at a content ratio of 7.2 mass ppm or more and 16 mass ppm or less, relative to the total mass of the methacrylic resin composition.
[0058] The resin molded body of the present embodiment is a plate-like molded body having a flat or concave curved surface or a convex curved surface, and at least a part of the region of the side end surface of the resin molded body is a light incident end surface, and at least one of the main surfaces of the resin molded body is a light exit surface. When the LED light source is emitted from the light exit surface, the luminance is measured at a point at the same distance from the light entrance position of the resin molded body, compared with a resin molded body of the same thickness that does not contain a light diffusing agent (i.e., a resin molded body produced with the same composition and method except that it does not contain a light diffusing agent). The luminance is preferably at least twice as high as that of a resin molded body of the same thickness that is produced with the same composition and method except that it does not contain a light diffusing agent, more preferably at least 2.5 times as high, and even more preferably at least 3 times as high. In order to obtain a luminance at least twice as high as that of a resin molded body of the same thickness that does not contain a light diffusing agent, the luminance can be adjusted by the above-mentioned type of light diffusing agent, the average particle size of the light diffusing agent, the content ratio of the light diffusing agent, the type of methacrylic resin, and the refractive index difference between the methacrylic resin and the light diffusing agent. The luminance measurement method will be described later.
[0059] In the resin molded product of this embodiment, the light diffusing agent can be the light diffusing agent described in the section on the methacrylic resin composition above.
[0060] In the resin molded body of this embodiment, the methacrylic resin may be the methacrylic resin described in the section on methacrylic resin compositions. A polycarbonate resin may be used from the viewpoint of excellent heat resistance and impact resistance. A methacrylic resin is preferred from the viewpoint of excellent transparency, brightness, and balance between transparency and brightness when titanium dioxide is used.
[0061] The lower limit of the thickness of the resin molded body of this embodiment is not particularly limited, and from the viewpoint of improving the brightness and mechanical properties of the resin molded body, it is preferably 1 mm or more, more preferably 2.0 mm or more, and even more preferably 2.5 mm or more. On the other hand, the upper limit of the thickness of the resin molded body is not particularly limited, and from the viewpoint of improving the transparency of the resin molded body and achieving a uniform surface and optical properties, it is preferably 20 mm or less, more preferably 10 mm or less, and even more preferably 10 mm or less.
[0062] (Method of manufacturing resin molded body) Examples of methods for obtaining the resin molded body of this embodiment include known molding methods such as known injection molding, extrusion molding, and pressure molding. The obtained resin molded body may be further molded using known molding methods such as pressure molding and vacuum molding. Molding conditions such as molding temperature and molding pressure may be appropriately set. In order to prevent deterioration and sublimation of the wavelength control agent, the temperature is preferably 300°C or less, more preferably 280°C or less, and even more preferably 270°C or less. In order to ensure good smoothness in the resin molded body and improve the dispersibility of the wavelength control agent, the temperature is preferably 200°C or more, more preferably 210°C or more, and even more preferably 200°C or more. Specifically, the pellet-shaped methacrylic resin composition obtained by the above-mentioned method for producing a methacrylic resin composition is dried at 70 to 100°C for 4 to 24 hours, and the moisture content of the dried methacrylic resin composition is adjusted to 0.1% or less based on the total mass of the methacrylic resin composition, and then the resin molded body of the present embodiment can be obtained by molding the composition using a known molding method such as a known injection molding method, an extrusion molding method, or a pressure molding method. Drying at 70 to 100° C. for 4 to 24 hours can suppress deterioration and coloration of the methacrylic resin composition due to heating, so that the resin molded product has excellent transparency and low coloration. By injection molding the methacrylic resin composition with a moisture content of 0.1% or less, relative to the total mass of the methacrylic resin composition, the resin molded article after injection molding is less likely to have appearance defects such as silver streaks, and it is possible to obtain a resin molded article with excellent transparency and good appearance.
[0063] <Combination lamp cover> The resin molded body of this embodiment is excellent in transparency, brightness, and balance between transparency and brightness. Therefore, the resin molded body of this embodiment is excellent in visibility because it emits high brightness when the light source is turned on by arranging a light source in at least a part of the region of the side end surface of the resin molded body, and has excellent design because it has transparency and a luxurious gloss when the light source is turned off. Therefore, it can be suitably used as a vehicle interior / exterior member, a lamp cover for an illumination lamp, and a light guide for a surface light source device, and can be particularly suitably used as a tail lamp cover, a stop lamp cover, a high-mount stop lamp cover, a rear lamp cover, or a rear combination lamp cover. In particular, it is more preferable that a resin molded body colored in white and / or a resin molded body coated with a metal vapor deposition film is arranged inside in order to improve external visibility. EXAMPLES
[0064] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0065] [Raw materials used in the examples and comparative examples] <Raw material for methacrylic resin> The raw materials for the methacrylic resin (A) used in the production of the thermoplastic resin composition are as follows. Methyl methacrylate (MMA): Asahi Kasei (containing 2.5 ppm by mass of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA): manufactured by Mitsubishi Chemical (containing 14 ppm by mass of 4-methoxyphenol manufactured by Kawaguchi Chemical Industry Co., Ltd. as a polymerization inhibitor) n-Octyl mercaptan: Arkema Lauroyl peroxide: NOF Corporation Perhexa 22: NOF Corp. Metaxylene: manufactured by Tokyo Chemical Industry Co., Ltd. - Tribasic calcium phosphate: Manufactured by Nippon Chemical Industry Co., Ltd., used as a suspending agent Calcium carbonate: Shiraishi Kogyo Co., Ltd., used as a suspending agent Sodium lauryl sulfate: Manufactured by Wako Pure Chemical Industries, used as a suspension aid
[0066] <Polycarbonate Resin Composition> Teijin Panlite L1250-Y
[0067] <Light diffusing agent> Light diffuser 1: SMM-22 made by Nippon Light Metal (aluminum oxide with an average particle size of 450 nm) Light diffuser 2: Ishihara Sangyo R-820 (titanium dioxide with an average particle size of 260 nm)
[0068] <Wavelength Adjustment Agent> Wavelength adjustment agent 1: LANXESS Macrolex Red EG (maximum absorption wavelength: 510 nm, perinone-based wavelength adjustment agent in which some of the hydrogen atoms in the chemical structure are replaced by halogen atoms) Wavelength adjuster 2: LANXESS Macrolex Red E2G (maximum absorption wavelength: 480 nm, perinone type wavelength adjuster) Wavelength adjuster 3: LANXESS Macrolex Red B (maximum absorption wavelength: 540 nm, azo-based wavelength adjuster) Wavelength adjuster 4: LANXESS Macrolex Yellow E2R (maximum absorption wavelength: 448 nm, quinophthalone wavelength adjuster)
[0069] <Other additives> Tinuvin P: BASF, melting point 128℃ Stearyl alcohol: Kao Kalcol 8098
[0070] <Measurement method> The evaluations in the examples and comparative examples were carried out by the following methods.
[0071] <Preparation of test piece A> The pellets of the methacrylic resin composition obtained in the examples and comparative examples were fed into an injection molding machine (Toshiba Machine EC100SX), and the molding temperature was set to 250°C, the mold temperature to 70°C, and the mold polishing grit was set to 8000 to obtain stepped test piece A (a stepped flat plate having a thickness of 1-3 mm x width 65 mm x length 102 mm, each step being 34 mm long).
[0072] <Preparation of test specimen 2> The pellets of the methacrylic resin compositions obtained in the Examples and Comparative Examples were fed to an injection molding machine (Toshiba Machine EC100SX), and the molding temperature was set to 260°C, the mold temperature was set to 68°C, and JIS dumbbell-shaped test pieces Type 1A test pieces were produced in accordance with JIS K7120. The obtained JIS dumbbell-shaped test pieces Type 1A test pieces were annealed at 83°C for 16 hours and conditioned at 23°C and a relative humidity of 50%RH for 24 hours before use.
[0073] <Preparation of test specimen 3> The pellets of the methacrylic resin compositions obtained in the examples and comparative examples were fed into an injection molding machine (Toshiba Machine EC100SX), and a flat test piece (thickness 3 mm x width 100 mm x length 100 mm) was obtained under the conditions of a molding temperature of 250°C, a mold temperature of 70°C, and a mold polishing grit of 8000.
[0074] <Light resistance> Using a Sunshine Carbon Arc Weather Meter manufactured by Suga Test Instruments, a 2000-hour test was conducted under conditions of a black panel temperature of 63°C and 18 minutes of rainfall out of 120 minutes. The long-term usage characteristics were evaluated by the color difference (ΔE) before and after the test at a thickness of 3 mm measured using a Nippon Denshoku TC8600 with a C light source and 10° field of view transmission mode. The flat specimens used were 100 mm x 100 mm x 3 mm flat specimens manufactured by the above-mentioned injection molding. If ΔE was 0.5 or less, it was rated as ◎ (excellent), if it was between 0.5 and 1.4, it was rated as ◯ (good), if it was between 1.4 and 1.8, it was △ (sufficient for practical use), and if ΔE exceeded 1.8, it was rated as × (poor).
[0075] <Impact strength> The result of the unnotched Charpy impact test conducted using a JIS dumbbell-shaped test piece Type 1A test piece in accordance with JIS K7111-1 was 20 kJ / m 2 Above 〇 (good), 17kJ / m 2 More than 20kJ / m 2 If it is less than 17kJ / m, it is △ (sufficient for practical use). 2 If it was less than 17 kJ / m, it was marked as × (bad). 2 If the above is true, a molded article having a good strength at the attachment portion to another member can be obtained.
[0076] <Brightness> A flat test piece or, in Example 13, a stepped test piece A instead of the flat test piece was placed on a test table installed in a darkroom, and the 3 mm x 100 mm surface or the 3 mm x 65 mm surface where no gate was present was used as the light incident surface, and a white LED edge light was placed adjacent to the light incident surface. The output of the light source was measured for luminance (cd / m2) from a position 60 mm away from the light incident surface in the incident direction and 200 mm above, using a luminance and chromaticity uniformity measuring instrument UA-10SL manufactured by Topcon Technohouse. 2 ) was measured. The luminance of the resin molded body produced based on each Example was compared with that of the resin molded body produced based on each Example, with the same composition and method as in each Example except that it does not contain a light diffusing material, and if the luminance of the resin molded body produced based on each Example is 2 times or more and less than 2.5 times that of the resin molded body produced based on the corresponding light diffusing material, it is rated as △ (sufficient for practical use), if it is 2.5 times or more and less than 3 times, it is rated as ◯ (good), if it is 3 times or more, it is rated as ◎ (excellent), and if the luminance of the resin molded body produced based on each Example is 2 times or more than that of the resin molded body produced based on the corresponding light diffusing material, it can be said to be a bright molded body with good visibility.
[0077] <Total light transmittance (Tt)> As an index of transparency of the resin molded body, the total light transmittance (%) of the stepped test piece A (thickness: 2 mm part, 3 mm part) was measured using a spectral colorimeter / haze meter (Nippon Denshoku COH7700) in accordance with JIS K7361, using the A light source 2 degree visual field transmission mode. Three test pieces were used, and one measurement was taken for each test piece, and the average value was taken as the total light transmittance (Tt). Furthermore, it was judged using the following criteria. If the total light transmittance was 16% or more, it was rated as ◯ (good), if it was 14% or more but less than 16%, it was rated as △ (sufficient for practical use), and if it was less than 14%, it was rated as × (bad). If the total light transmittance was 14% or more, it was possible to obtain a molded product with gloss and transparency.
[0078] <Haze value (H)> As an index of transparency of the resin molded body, the haze value (%) of stepped test piece A (thickness: 2 mm part, 3 mm part) was measured using a spectrophotometric colorimeter (COH7700 manufactured by Nippon Denshoku) in accordance with JIS K7361, using light source A and 2 degree visual field transmission mode. Three test pieces were used, and one measurement was taken for each test piece, and the average value was taken as the haze value (H). Furthermore, it was judged using the following criteria. If the haze value was 6% or less, it was rated as ◯ (good), if it was between 6% and 11% or less, it was △ (sufficient for practical use), and if it was over 11%, it was rated as × (bad). If the haze value was 11% or less, it was possible to obtain a molded product with gloss and transparency.
[0079] <Heat deformation resistance> As an index of heat deformation resistance, the Vicat softening temperature was measured using a JIS dumbbell-shaped test piece Type 1A test piece according to JIS K7206 B50 method. As an index of heat deformation resistance, a temperature of 104°C or higher was judged as ◯ (good), a temperature of 100°C or higher but less than 104°C was judged as △ (sufficient for practical use), and a temperature of less than 100°C was judged as × (not suitable for vehicle use). By keeping the temperature at 100°C or higher, it is possible to obtain a molded product that can maintain its dimensions even when exposed to heat from a light source or heat from sunlight.
[0080] <Yellowness (YI)> As an index of the transparency of the test piece, using a spectroscopic color and haze meter (COH7700 manufactured by Nippon Denshoku), in accordance with ISO17223, in the C light source 2-degree field of view transmission mode, the yellowness of the stepped test piece A (thickness: 3 mm part, 2 mm part) was measured. Using three test pieces, each test piece was measured once, and the average value was taken as the yellowness (YI).
[0081] <H / Tt value, YI / H value> From the total light transmittance (Tt), haze value (H), and yellowness (YI), the H / Tt value and YI / H value were calculated.
[0082] <Production Example 1 (Production of methacrylic resin 1)> Into a container equipped with a stirrer, 2 kg of ion-exchanged water, 65 g of tricalcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate were added to obtain a mixed solution. Next, 26 kg of ion-exchanged water was added to a 60 L reactor and heated to 80 °C, and then the total amount of the mixed solution, 21.1 kg of methyl methacrylate, 0.42 kg of methyl acrylate, 27 g of lauroyl peroxide, and 56 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining at about 80 °C. After observing the exothermic peak, the temperature was raised to 92 °C at a rate of 1 °C / min and aged for 60 minutes to substantially complete the polymerization reaction. Next, in order to cool to 50 °C and dissolve the suspending agent, 20 mass% sulfuric acid was added, and then the polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove aggregates. The obtained bead-like polymer was washed, dehydrated, and dried to obtain polymer fine particles (methacrylic resin 1). The weight average molecular weight of the obtained resin was 106,000, the molecular weight distribution (Mw / Mn) was 1.85, and the abundance of the molecular weight component below 1 / 5 of the peak top molecular weight (Mp) was 4.3%. Also, the monomer unit was MMA / MA = 98 / 2 mass%, and the amount of unsaturated bond terminals was 0.008 mol%.
[0083] <Production Example 2 (Production of methacrylic resin 2)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 26 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and the entire mixture, 21.3 kg of methyl methacrylate, 2.3 kg of methyl acrylate, 65 g of lauroyl peroxide, and 70 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles (methacrylic resin 2). The Mw of the obtained methacrylic resin was 92,000, the molecular weight distribution (Mw / Mn) was 1.86, and the abundance (%) of molecular weight components with a molecular weight of 1 / 5 or less of the Mp value was 4.6%. The monomer unit was MMA / MA=90 / 10% by mass, and the amount of unsaturated double bond terminals was 0.008 mol%.
[0084] <Production Example 3 (Production of Methacrylic Resin 3)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 26 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and the entire mixture, 20.5 kg of methyl methacrylate, 1.32 kg of methyl acrylate, 33 g of lauroyl peroxide, and 28.5 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80°C, and after observing an exothermic peak, the temperature was increased to 92°C at a rate of 1°C / min. Thereafter, the mixture was aged for 60 minutes to essentially complete the polymerization reaction. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles (methacrylic resin 3). The weight average molecular weight of the resin obtained was 186,000, the molecular weight distribution (Mw / Mn) was 1.85, the amount of molecular weight components with molecular weights of 1 / 5 or less of the peak top molecular weight (Mp) was 4.3%, the monomer units were MMA / MA=94 / 6 mass%, and the amount of unsaturated bond terminals was 0.009 mol%.
[0085] <Production Example 4 (Production of Methacrylic Resin 4)> Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid. Next, 26 kg of ion-exchanged water was added to a 60 L reactor, and the temperature was raised to 80° C., and the entire mixed liquid, 21.2 kg of methyl methacrylate, 0.43 kg of methyl acrylate, 27 g of lauroyl peroxide, and 88 g of n-octyl mercaptan were added. Thereafter, suspension polymerization was carried out while maintaining the temperature at about 80° C., and after observing an exothermic peak, the temperature was raised to 92° C. at a rate of 1° C. / min, and the mixture was aged for 60 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh sieve to remove agglomerates, and the resulting bead-like polymer was washed, dehydrated and dried to obtain polymer microparticles (methacrylic resin 4). The weight-average molecular weight of the resin obtained was 73,000, the molecular weight distribution (Mw / Mn) was 1.85, and the abundance of molecular weight components with molecular weights of 1 / 5 or less of the peak top molecular weight (Mp) was 4.7%. The monomer units were MMA / MA=98 / 2 mass%, and the amount of unsaturated bond terminals was 0.007 mol%.
[0086] [Examples 1 to 12] [Comparative Examples 1 to 5] The methacrylic resin, polycarbonate resin composition, light diffusing agent, wavelength adjusting agent, Tinuvin P 400 mass ppm and Kalcol 8098 1500 mass ppm were weighed out so as to obtain the blending ratios shown in Table 1, and then charged into a tumbler and mixed. After thorough mixing, the mixed raw materials were charged into a φ26 mm twin-screw extruder, melt-kneaded (compounded) to generate strands, cooled in a water bath, and cut with a pelletizer to obtain pellets. During compounding, a vacuum line was connected to the vent of the extruder, and volatile components such as moisture and monomer components were removed under conditions of -0.08 MPa. Thus, a methacrylic resin composition was obtained. The kneading temperature of the resin composition was 220°C for Examples 9 and 10, 260°C for Example 5, 280°C for Comparative Example 5, and 240°C for the others. The numerical values in Table 1 indicate the number of blended parts (parts by mass) when the mass of the methacrylic resin and polycarbonate resin composition is 100 parts by mass. In Example 13, evaluation was performed on the 2 mm thick portion of the stepped test piece A of Example 6. The results of evaluation of each Example are shown in Table 1.
[0087] [Table 1]
[0088] In Examples 1 and 3 to 7, it was possible to obtain methacrylic resin compositions having an excellent balance between transparency and brightness, as well as excellent light resistance, impact strength, and heat deformation resistance, and molded articles made of the same. Comparative Example 1 had poor luminance because it did not contain a light diffusing agent. In Comparative Example 2, the amount of the wavelength adjusting agent was excessive, so the brightness and total light transmittance were poor, and the light resistance was also somewhat poor. In Comparative Example 3, the total light transmittance and haze were not good, the transparency was poor, and the impact strength was also somewhat poor. The brightness was not good in Comparative Example 4. The light resistance of Comparative Example 5 was not good, and the total light transmittance was also somewhat poor. Example 2 was at a practically sufficient level, but the total light transmittance was slightly inferior to the other examples, and the transparency was slightly inferior. Example 8 was at a practically sufficient level, but was somewhat inferior to the other examples in total light transmittance and brightness. Example 9 was at a practically sufficient level, but the heat distortion resistance was slightly inferior to the other examples. Example 10 was at a practically sufficient level, but the impact strength was slightly inferior to the other examples. Examples 11 and 12 were at a level sufficient for practical use, but the light resistance was slightly inferior to the other examples.
[0089] The methacrylic resin composition of the present embodiment is a colored resin composition and a molded article that have an excellent balance between transparency and brightness, and also has excellent light resistance, impact strength, and heat deformation resistance, and has the potential for industrial use as, but not limited to, edge-illuminated display panels and lamp covers. In particular, it has potential for favorable industrial use as vehicle lamp covers such as tail lamp covers, stop lamp covers, high-mount stop lamp covers, rear lamp covers, and rear combination lamp covers.
Claims
1. A methacrylic resin, A light diffusing agent having an average particle size of 200 nm or more and 700 nm or less; At least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents, which have a maximum absorption wavelength at a wavelength of 440 to 600 nm in a wavelength range of 380 to 780 nm; Contains The mass ratio of the light diffusing agent is more than 4.0 ppm by mass and less than 90 ppm by mass with respect to 100% by mass of the methacrylic resin composition, The mass ratio of the wavelength adjusting agent is 300 ppm by mass or more and less than 6000 ppm by mass with respect to 100% by mass of the methacrylic resin composition; A methacrylic resin composition comprising:
2. 2. The methacrylic resin composition according to claim 1, wherein the methacrylic resin contains 90% by mass or more and 99.9% by mass or less of methyl methacrylate monomer units and 0.1% by mass or more and 10% by mass or less of other vinyl monomer units copolymerizable with methyl methacrylate, relative to 100% by mass of the methacrylic resin, and has a weight average molecular weight of 90,000 or more and 200,000 or less.
3. The methacrylic resin composition according to claim 2, having a Vicat softening temperature of 102°C or higher and 130°C or lower.
4. A resin molded product obtained by molding a methacrylic resin composition containing a methacrylic resin, a light diffusing agent having an average particle size of 200 nm to 700 nm in an amount of 2 ppm by mass to 90 ppm by mass, and at least one wavelength adjusting agent selected from the group consisting of azo-based, anthraquinone-based, perinone-based, methine-based, and quinophthalone-based agents having a maximum absorption wavelength in a wavelength range of 440 to 600 nm within a wavelength range of 380 to 780 nm, A total light transmittance (Tt) in the thickness direction measured in accordance with ISO 13468 is 14% or more and less than 30%; The haze value (H) in the thickness direction measured in accordance with ISO 14782 is 1.0% or more and 11% or less, and A resin molded product, characterized in that the yellowness index (YI) in the thickness direction, the total light transmittance (Tt), and the haze value (H), measured in accordance with ISO 17223, satisfy the following formulas (1) and (2): 0.11≦H / Tt≦0.8 (1) 25≦YI / H≦150 (2)
5. The resin molded article according to claim 4, which is used as a tail lamp cover, a stop lamp cover, a high mount stop lamp cover, a rear lamp cover, or a rear combination lamp cover.
Citation Information
Patent Citations
Lamp fitting for vehicle
JP2012064533A
Transparent resin composition, resin molded body, lamp cover, lamp cover for vehicles, combination lamp cover, and vehicle
WO2019172243A1